2023
DOI: 10.1186/s41935-023-00331-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity associated with acute and chronic administration of synthetic cannabinoids “Strox” in the brain, liver, heart, and testes of male albino rats: histological and immunohistochemical study

Abstract: Background Synthetic cannabinoids are one of the largest groups of new psychoactive substances that invaded Egypt’s drug abuse market over the past few years. Aim Randomized controlled trial study to demonstrate the effects of acute and chronic toxicity by synthetic cannabinoid (Strox) on the brain, liver, heart, and testes in adult male albino rats through histopathological examination by light microscope and immunohistochemistry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, the histopathological results of the present study are close to those reported in acute toxicity studies of other SCs, as mentioned by Abass et al [ 23 ] and Bakdash et al [ 24 ], who explored the LD 50 of voodoo extract and THJ-2201 in rodents. Similarly, Abdelmoneim et al [ 41 ] mentioned comparable results after chronic oral administration of Strox in Rats. The biochemical assay in the present study showed an increase in serum AST in the higher-dose group and no change in serum ALT which can be explained by injecting low doses of AB-CHMINACA and the liver's capacity to compensate for damage to an extent to preserve its function.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, the histopathological results of the present study are close to those reported in acute toxicity studies of other SCs, as mentioned by Abass et al [ 23 ] and Bakdash et al [ 24 ], who explored the LD 50 of voodoo extract and THJ-2201 in rodents. Similarly, Abdelmoneim et al [ 41 ] mentioned comparable results after chronic oral administration of Strox in Rats. The biochemical assay in the present study showed an increase in serum AST in the higher-dose group and no change in serum ALT which can be explained by injecting low doses of AB-CHMINACA and the liver's capacity to compensate for damage to an extent to preserve its function.…”
Section: Discussionmentioning
confidence: 72%
“…The biochemical assay in the present study showed an increase in serum AST in the higher-dose group and no change in serum ALT which can be explained by injecting low doses of AB-CHMINACA and the liver's capacity to compensate for damage to an extent to preserve its function. Furthermore, AST is elevated not only by liver damage but by other organ affection, such as the heart and muscles, which is expected to be present [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%